AL- Adah al-Mutadah (traditions) of Christian monasteries in the city of Jerusalemduring the eighteenth and nineteenth centuries (Damascus University Journal of Historical Studies, 2025)
This study aims to investigate one of the financial assumptions of Christian monasteries in the city of Jerusalem during the eighteenth and nineteenth centuries AD, and it is known AL-Adah  al-Mutadah ( traditions). The study dealt with the groups benefiting from the usual custom and the three Christian monasteries that were paid by them (the Armenian Monastery, the Latin Monastery and the Deir al-Rum), and concluded by talking about the attempts made to abolish them. In view of the fact that the documents constitute a preeminence in the construction of the historical text, this study relied on a unique type of historical documents represented by the records of the Al-Quds Sharia Court because of the rich and rich information they provide on the subject of the study, and it was unique to other sources, whether printed or manuscript, in dealing with the documents of the usual custom. In this study, the researcher used several approaches, the most important of which is the historical-analytical method, and he also relied on the quantitative-statistical method through the statistical method that is based on the collection of digital data.
Keywords: Jerusalem; Christians; AL- Adah al; Mutadah (traditions); The eighteenth century; The nineteenth century